2004
DOI: 10.1128/jvi.78.23.13376-13380.2004
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenicity of Virulent Marek's Disease Virus Cloned as Bacterial Artificial Chromosomes

Abstract: Marek's disease virus (MDV) is an oncogenic alphaherpesvirus that induces T-cell lymphomas in poultry.We report the construction of bacterial artificial chromosome (BAC) clones of the highly oncogenic RB-1B strain by inserting mini-F vector sequences into the U S 2 locus. MDV reconstituted from two BAC clones induced rapid-onset lymphomas similar to those induced by the wild-type virus. Virus reconstituted from another BAC clone that showed a 7.7-kbp deletion in the internal and terminal unique long repeat reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
109
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(111 citation statements)
references
References 7 publications
1
109
0
1
Order By: Relevance
“…Although whether or not REV-LTR insertion affects the in vivo expression of MDV-1-encoded miRNAs is unknown as yet, our research may provide meaningful clues for further evaluating their functions, especially for the twelve miRNAs highlighted in this study. Based on the successful establishment of strategies for mRNA target prediction and experimental identification (Kuhn et al, 2008;Alexiou et al, 2009;Bartel, 2009), and the application of bacterial artificial chromosomes in research on MD pathogenesis (Schumacher et al, 2000;Petherbridge et al, 2003Petherbridge et al, , 2004Sun et al, 2009Sun et al, , 2010, focusing on those miRNAs shown to be expressed in vivo in this study should reveal more about the biological functions of MDV-1-encoded miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Although whether or not REV-LTR insertion affects the in vivo expression of MDV-1-encoded miRNAs is unknown as yet, our research may provide meaningful clues for further evaluating their functions, especially for the twelve miRNAs highlighted in this study. Based on the successful establishment of strategies for mRNA target prediction and experimental identification (Kuhn et al, 2008;Alexiou et al, 2009;Bartel, 2009), and the application of bacterial artificial chromosomes in research on MD pathogenesis (Schumacher et al, 2000;Petherbridge et al, 2003Petherbridge et al, , 2004Sun et al, 2009Sun et al, , 2010, focusing on those miRNAs shown to be expressed in vivo in this study should reveal more about the biological functions of MDV-1-encoded miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…This opportunity has been possible because of the availability of the infectious BAC clone of the highly oncogenic RB-1B strain of MDV (19), which allows the application of mutagenesis techniques for the rapid generation of mutant viruses. Pathogenicity studies in susceptible inbred and outbred chickens clearly demonstrated that MEQ-CtBP interaction is crucial for the induction of lymphomas because the pRB-1B-Ct20 virus with mutation in the MEQ genes that abolished the interaction with CtBP was completely nononcogenic.…”
Section: Discussionmentioning
confidence: 99%
“…A DF-1 cell line derived from line 0 chicken embryonic fibroblasts (27) was used for immunoprecipitation and reporter assays. The very virulent RB-1B strain of MDV originally obtained from K. A. Schat (Cornell University, Ithaca, NY) and the BAC-derived pRB-1B5 viruses (19) were used in pathogenicity tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…pCVI988-10 and Poulvac CVI988 both give 100% protection against mortality following infection with a vvMDV strain (28). Group 3 received pRB-1B-2, a BAC-cloned experimental virus which is derived from vvMDV strain RB-1B (31) but has genomic deletions that result in a loss of pathogenicity and oncogenicity (27). Group 4 received a bivalent vaccine, HVT+SB-1 (Marexine, Intervet).…”
Section: Methodsmentioning
confidence: 99%